Respuesta :
Answer:
hey there the answer is:
Step-by-step explanation:
3x(x)+3x(8) + 7(x)+7(8)
3x^2+24x+7x+56=
56+31x+3x²
Answer:
3x^2+31x+56
Step-by-step explanation:
First, we need to multiply using the FOIL (first, outer, inner, last) method.
Let's multiply the first terms together:
3x(x)=3x^2
Now we multiply the outer terms:
3x(8)=24x
Next we multiply the inner terms:
7(x)=7x
Finally, we need to multiply the last terms:
7(8)=56
Now we have this:
3x^2+7x+24x+56
Combine like terms:
3x^2+31x+56
HTH :)